吉西他滨调整方案治疗晚期非小细胞肺癌的Ⅱ期临床试验 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: Gemcitabine-platinum-combined with chemotherapy is the most common treatment for advanced non-small cell lung cancer (NSCLC). Gemcitabine is administered once a week in a general three-week schedule. In the present study, gemcitabine is administered on d1 and d5 to improve compliance, and the efficacy and safety of the improved regimen is evaluated in untreated patients with advanced NSCLC. METHODS: A total of 83 patients were enrolled between October 2007 and October 2009. In each cycle, gemcitabine was administered at a dose of 1, 000 mg/m(2)-1, 250 mg/m(2) via a 30 min intravenous infusion on d1 and d5 followed by cisplatin at a dose of 75 mg/m(2) or carboplatin (AUC=5) on d1 every three weeks. At least two cycles of chemotherapy were completed in each case, and clinical response and toxicity of the regimen were observed. RESULTS: The objective response rate was 37.3%. The median progression free survival and overall survival time were 6.1 months and 15.0 months, respectively. The one-year and two-year survival rates were 57.8% and 16.2%, respectively. Myelosuppression and gastrointestinal responses were the main toxicities. The incidence of grade 3/4 of leucopenia, hypohemia, and thrombocytopenia were 26.5%, 10.8% and 7.2%, respectively. A total of 27.5% of the patients in the cisplatin group had grade 3/4 gastrointestinal responses. Treatment related deaths were not observed in this study. CONCLUSION: The regimen is active and well-tolerated in untreated patients with advanced NSCLC. Further randomized controlled studies are necessary.